ANALISIS FAKTOR DETERMINASI PENANAMAN MODAL ASING (PMA) LANGSUNG DI ASEAN - Dwi Resti Pratiwi (Pusat Kajian Anggaran, 2020)
The number of Foreign Direct Investment (FDI) in ASEAN has been increasing over the past years. FDI is one of the sources of investment that is really important, mainly for developing countries. This research aims to analyse the development and determinants of Foreign Direct Investment (FDI) inflows in ASEAN countries over the period 2007 to 2018. It focused on six members of ASEAN countries including Indonesia, Singapore, Malaysia, Thailand, Philipines and Vietnam. By using data panel analysis with common effect model, it indicates that market size, exchange rate, trade openness, and political stability, were significant and positively attracted FDI inflow in ASEAN. Additionally, real interest rate was significantly proven to have negative effect on FDI Inflow. Meanwhile, inflation rate was not significant in attracting FDI to the region. This result shows that macroecenomic indicators are the key factors that attract more FDI. So that, the Government of ASEAN Countries have to maintain macroeconomic stability in encouraging more investors to the ASEAN countries. Beside that, political risk and uncertainty has to be minimized by increasing the political stability and good control of corruption in order to create condusive investment environment for foreign investors.